The Role of Adherence to Basic Pharmacotherapy of Heart Failure for Prevention of Late Adverse Events in Patients with Coronary Artery Disease and Left Ventricular Dysfunction After Surgical Revascularization of Myocardium - O. A. Yepanchintseva; K. A. Mikhaliev; I. V. Shklianka; O. J. Zharinov; B. M. Todurov (Столичная издательская компания, 2020)
Aim. To determine the role of adherence to the basic drug treatment of heart failure (HF) in prevention of late major adverse events (MAEs) after isolated coronary artery bypass grafting (CABG) in patients with stable coronary artery disease (CAD) and left ventricular (LV) dysfunction at three-year follow-up.Material and methods. A prospective non-controlled single-center study included 125 consecutive patients with stable CAD and LV EF<50% (62±8 years; 114 [91.2%] males), after isolated CABG. At three-year follow-up MAЕs occurred in 40 (32.0%) patients. The data on pharmacotherapy at followup were obtained in 124 patients: 85 (68.6%) patients without MAEs and 39 (31.4%) patients with MAEs.Results. The enrolled sample of patients was characterized by high discharge prescription rate of renin-angiotensin system (RAS; 86.3%) blockers (angiotensin-converting enzyme inhibitors or angiotensin-II receptors blockers), beta-blockers (BBs; 97.6%) and mineralocorticoid receptors antagonists (MRAs; 79.0%), being comparable in MAEs and non-MAEs groups. The total coverage of basic HF pharmacotherapy (the combination of RAS blockers, BBs and MRAs) at discharge was 66.1%. At follow-up, about one third of patients in both groups withheld previously prescribed triple HF therapy. The MAEs were associated with more frequent withhold of previously prescribed RAS blockers, as opposed to patients without MAEs (20.5% and 7.1%, respectively; р=0.009). The majority of patients in both groups continued BBs therapy at follow-up (95.0% and 92.9%, respectively; p=0.187). Additionally, we observed the decline of MRAs intake frequency at follow-up (to 43.6% and 49.4%, respectively; p=0.547).Conclusion. During 3-year follow-up after isolated CABG, about one third of patients with stable CAD and baseline LVEF<50% interrupted triple basic HF therapy (including RAS blockers, BBs and MRAs), mainly due to decrease of RAS blockers and MRAs usage. MAEs in patients with stable CAD and baseline LVEF<50% after CABG were associated with suboptimal use and more frequent interruption of RAS blockers.